Nucleation and dynamics of Golgi-derived microtubules - Sanders, Anna A.; Kaverina, Irina (Frontiers in Neuroscience, 2015)
Integrity of the Golgi apparatus requires the microtubule (MT) network. A subset of MTs originates at the Golgi itself, which in this case functions as a MT-organizing center (MTOC). Golgi-derived MTs serve important roles in post-Golgi trafficking, maintenance of Golgi integrity, cell polarity and motility, as well as cell type-specific functions, including neurite outgrowth/branching. Here, we discuss possible models describing the formation and dynamics of Golgi-derived MTs. How Golgi-derived MTs are formed is not fully understood. A widely discussed model implicates that the critical step of the process is recruitment of mo-lecular factors, which drive MT nucleation (γ-tubulin ring complex, or γ-TuRC), to the Golgi membrane via specific scaffolding interactions. Based on recent findings, we propose to introduce an additional level of regulation, whereby MT-binding proteins and/or local tubulin dimer concentration at the Golgi helps to overcome kinetic barriers at the initial nucleation step. According to our model, emerging MTs are subsequently stabilized by Golgi-associated MT-stabilizing proteins. We discuss molecular factors potentially involved in all three steps of MT formation. To preserve proper cell functioning, a balance must be maintained between MT subsets at the centrosome and the Golgi. Recent work has shown that certain centrosomal factors are important in maintaining this balance, suggesting a close connection between regulation of centrosomal and Golgi-derived MTs. Finally, we will discuss potential functions of Golgi-derived MTs based on their nucleation site location within a Golgi stack.